Kajian Kitab Ta’lim Muta’allim di Sukolilo Labang - Abdurrohman; Umar Zakka (PT. ALHAFI BERKAH INDONESIA, 2023)
This report on the results of community service discusses the study of the book Ta'lim al Muta'allim in Sukolilo Labang. In studying the book of ta'lim, it is not just about conveying theory but must contain elements of theory and practice. Study the book of ta'lim to practice it. If it contains orders or commands, it must be able to be implemented, if it contains prohibitions, it must be abandoned or avoided. Therefore, this study of ta'lim is not only to be known, but to be practiced and at the same time become a guide or guide for life. For this reason, of course material that is practical for everyday practice takes priority in the implementation of learning. The aim of holding this Muta'allim ta'lim book study activity is so that the community, especially teenagers, can pay attention to attitudes and be able to instill a polite and ethical spirit in interacting with others which then creates a beautiful life filled with noble morals. From this community service activity, it can be concluded that the Labang community's ability to understand religion, especially the application of good morals, has increased.